Corona Virus Impact on Indian Stock Market and Industry during Pandemic: A Case Study - GUPTA, DR. PRATEEK; AGARWAL, RACHIT; SINGHAL, RAHUL (The journal of contemporary issues in business and government, 2021)
Case Description: The primary subject matter of this case was to analyze the impact of novel Corona Virus (COVID’19), the worldwide pandemic on Indian investors with analyzing gains and losses (if any). The case also highlighted its impact on the Indian Stock Market’s various sectors and industries for two months (January 23, 2020 to March 23, 2020) and predictive industrial analysis. The discussion included an analysis of NSE and BSE’s indices focusing four sectors during lockdown in India, and the Indian government’s action during this pandemic situation. The market had been faced a downturn in between these two months; transportations and logistics industries had also been reported as a major decline. Furthermore, the case also included an examination of problems that arise in the Indian stock market like Indian investors’ gain or loss, financial strategies for corrective action and opportunities and challenges available for listed companies. The list of assigned questions and suggested solutions will lead students through this pandemic impact on the Indian financial market and will prepare them to make strategic recommendations. This case can be discussed in 90 minutes session and give insight into the stock market movements and industrial changes due to COVID’19. Case Synopsis: The novel Corona Virus (COVID’19) was a worldwide pandemic declared by the World Health Organization (WHO). This was detected by China in its Wuhan city in December 2019. This pandemic has been impacted the whole world very rapidly majorly in China, Italy, USA, Spain, France, Germany and India. As per the collected data, more than 1,929,633 people affected worldwide and 10,981 cases reported in India. The government of India announced curfew and lockdown time to time for the country’s prevention. In between these two months, India has faced many intense challenges in different ways such as downfall in the Indian financial market, nationwide lockdown, industrial changes, consumption rate, deaths etc. due to the pandemic. India also faced financial and economical issues due to this investors’ investing patterns affected by COVID’ 19.